2021
DOI: 10.1016/j.jmh.2020.100013
|View full text |Cite
|
Sign up to set email alerts
|

Perceived mental health, wellbeing and associated factors among Nepali male migrant and non-migrant workers: A qualitative study

Abstract: Background Poor mental health and illness among the working population have serious socioeconomic and public health consequences for both the individual and society/country. With a dramatic increase in work migration over the past decades, there is recent concern about the health and wellbeing of migrant workers and their accessibility to healthcare services in destination countries. This study aimed to explore the mental health and wellbeing experiences of Nepali male returnee-migrants and non-mi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 24 publications
(24 reference statements)
1
18
0
Order By: Relevance
“…Both occupational hazard and poor working environment have increased the vulnerability of migrant workers to poor health outcomes, especially on their mental well-being. Previous research indicated that migrant workers reported experiencing higher mental health problems in comparison to native workers [ 9 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both occupational hazard and poor working environment have increased the vulnerability of migrant workers to poor health outcomes, especially on their mental well-being. Previous research indicated that migrant workers reported experiencing higher mental health problems in comparison to native workers [ 9 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis found that 47% and 22% of labour migrants globally experienced occupational morbidity and workplace injury or incident, respectively 12. A study of Nepali labour migrants returning from the Gulf and Malaysia concluded that non-compliance with labour agreements, abuse and exploitation by supervisors, lack of privacy, and crowded accommodation made them vulnerable to mental health conditions 13…”
Section: Labour Migrants’ Healthmentioning
confidence: 99%
“…Health problems are rooted in the financial, familial, living, and working conditions related to being a temporary labour migrant 1113. Aside from the health of labour migrants themselves, research has shown that the children they leave behind are at risk of depression, suicidal ideation, and anxiety 14…”
Section: Labour Migrants’ Healthmentioning
confidence: 99%
See 2 more Smart Citations